THEORETICAL PERSPECTIVES AND CONCEPTUAL FRAMEWORKS OF COOPETITION - Suzanna zanna Lamria Siregar (Jurnal Ilmiah Ekonomi Bisnis, 2011)
There are several perspectives that provide useful theoretical frameworks foranalyzing coopetition based on its original paradigm – competition and cooperation.They are transaction–cost economics, resource-based view, game theory, industrialorganization,socioeconomics and social network analysis. Theoretical perspectivesthen developed to conceptual frameworks that explain and predict empiricalphenomena of coopetition. The frameworks of coopetition vary from a continuum withcooperation and competition at its ends to the tendency to adopt multidimensionalityunder orthogonal structure between two constructs of competition and cooperation. –briefly drawing the typology of coopetition with coopetition and cooperationconstructs as its axis.